Don't know much about history : everything you need to know about history but never learned - Davis, Kenneth C. (Davis, Kenneth C. Don't know much about., 2011)
Davis has brought his groundbreaking work up to the present, including the history of an "Era of Broken Trust," from the end of the Clinton administration through the recent Great Recession. This additional material covers the horrific events of 9/11 and the rise of conspiracy theorists, the wars in Iraq and Afghanistan, Hurricane Katrina and the failure of the New Orleans levees, the global financial meltdown, the election of Barack Obama, and the national controversy of same-sex marriage.